COMPETITIVENESS OF THE ECONOMY OF KAZAKHSTAN IN THE FRAMEWORK OF INTERNATIONAL INTEGRATION - Утеулина, Г.Н.; Омарова, З.К. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
This article examines the prospects for increasing and competitiveness of the national economy, as well as changing conditions, forms and methods of competition in the context of the country's integration into international organizations. The author defines the factors of regional competitiveness of enterprises such as increasing production, improving product quality, as well as the implementation of state policy in the field of increasing the competitiveness of the economy of Kazakhstan in the context of integration.